2021
DOI: 10.3390/biology10030187
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study Regarding Possible Side Effects of Miniscrew-Assisted Rapid Palatal Expander (MARPE) with or without the Use of Corticopuncture Therapy

Abstract: The use of maxillary expanders has the effect of distancing the maxillary bones at the level of the median palatal suture. During maxillary expansion, the main resistance forces occur at the zygomatico-maxillary sutures, and not in the median palatal suture, which is the basic principle on which this method is based. In this observational study, we evaluated possible complications at the skeletal and dentoalveolar level after palatal split using miniscrew-assisted rapid palatal expansion (MARPE) associated or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The most frequent complication observed using MARPE were inflammation and hyperplasia of the mucosa around the miniimplant/screw or loosening or deformation of the screws used. A decrease in bone level and thickness at first molars was observed in 41% and undesirable effects like ulcerations, oedema of the palatal mucosa were observed in 22% of cases [ 15 ]. In a retrospective study on 69 patients, 5% of the miniscrews dislodged during expansion and 13% showed clinically visible mobility [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent complication observed using MARPE were inflammation and hyperplasia of the mucosa around the miniimplant/screw or loosening or deformation of the screws used. A decrease in bone level and thickness at first molars was observed in 41% and undesirable effects like ulcerations, oedema of the palatal mucosa were observed in 22% of cases [ 15 ]. In a retrospective study on 69 patients, 5% of the miniscrews dislodged during expansion and 13% showed clinically visible mobility [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent complication observed using MARPE were in ammation and hyperplasia of the mucosa around the miniimplant/screw or loosening or deformation of the screws used. A decrease in bone level and thickness at rst molars was observed in 41% and undesirable effects like ulcerations, oedema of the palatal mucosa were observed in 22% of cases [14]. In a retrospective study on 69 patients, 5% of the miniscrews dislodged during expansion and 13% showed clinically visible mobility [15].…”
Section: Discussionmentioning
confidence: 99%
“…In adults it represents a treatment solution that can potentially reduce the complications of SARPE and is minimally invasive, secure, and reliably stable [11]. However, when MARPE is used with a rapid continuously opening expansion protocol in adult patients (two activations per day, achieving 0.4mm), the overload of the hardware (appliance and miniscrews) or of the involved anatomical structures can lead to unsatisfactory results [12][13][14][15]. In order to reduce these side effects, the rigidity of the expander used in this current study was improved and a novel 2-stage protocol was applied for miniscrew assisted palatal expansion (without Rapid expander activation) (MAPE) [16].…”
mentioning
confidence: 99%
“…Several intraoral tooth-borne appliances for Class II correction do not require patient compliance, but all of them are inevitably affected by loss of anterior anchorage [25] . Despite some reports of complications after the use of a bone-borne rapid maxillary expander, including eye impairment, orbital microfracture, facial asymmetry [26] , and other issues [27] , the risk of these undesired phenomena was reduced by planning a gentle screwactivation protocol (1 turn/day) and monitoring this phase weekly. Moreover, the patient is a young adult, and therefore highly unlikely to encounter these complications, which are usually corre-Please cite this article as: M. Palone et al, Class II treatment of transverse maxillary deficiency with a single bone-borne appliance and hybrid clear aligner approach in an adult patient: a case report, Journal of the World Federation of Orthodontists, https://doi.org/10.1016/ j.ejwf.2021.12.004 lated with advanced skeletal maturity and increased bone density [28] .…”
Section: Discussionmentioning
confidence: 99%